Предмет: Алгебра,
автор: 141516
Помогите решить буду благодарна
Приложения:
Ответы
Автор ответа:
0
Смотри ///////////////////
Приложения:
Автор ответа:
0
2х+1-4√2х-1=-3
2х+1+3=4√2х-1
2х+4=4√2х+1
2(х+2)=4√2х+1
х+2=2√2х+1
(х+2)²=(2√2х+1)²
х²+4х+4=4(2х+1) х²+4х+4=8х+4 х²-4х=0 х(х-4)=0 х=0 х-4=0 х=4
Ответ: х1=0 х2=4
2х+1+3=4√2х-1
2х+4=4√2х+1
2(х+2)=4√2х+1
х+2=2√2х+1
(х+2)²=(2√2х+1)²
х²+4х+4=4(2х+1) х²+4х+4=8х+4 х²-4х=0 х(х-4)=0 х=0 х-4=0 х=4
Ответ: х1=0 х2=4
Приложения:
Похожие вопросы
Предмет: Литература,
автор: ylibashkasmail3
Предмет: География,
автор: olesazuravel91
Предмет: Химия,
автор: toha5757
Предмет: Физика,
автор: simbat00
Предмет: Математика,
автор: milpops